The practices of local cosmetic product on the customer loyalty among Malaysian youth / Nareesa Noorham, Sharifah Nurafizah Syed Anuar and Hasnawati Guliling - Noorham, Nareesa; Syed Anuar, Sharifah Nurafizah; Guliling, Hasnawati (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Over the past decades, skin care products with whitening and lightening function have been introduced to the Asian market and have been recognized as the best-selling product categories in the Asian beauty industry included Malaysia. The needs and desires of people to be beautiful should be the same throughout the world. People will gain confidence and stand in front of crowds without fear with the aid of the beauty product. The first impressions given to people in this modern society are crucial. People are increasingly emphasis on the appearance rather than other more durable criteria and emphasize on the shape of the female body, with the aids of the fashion and cosmetic products. Based on this reason, the desire to be beautiful has become increase until they are willing to take a risk by using the product that contains harm ingredients to appear beautiful in a short time. Although various ways have been done by the Ministry of Health to combat the use of dangerous products, it is very suprising that consumers are still loyal to use this product. Therefore, this study is to investigate what are the factors that influence customer loyalty towards cosmetic industry especially into skincare consumerism among Malaysian Youth. Hence, this paper intends to review past literature and develop a conceptual framework that will investigate the relationship between the practices in cosmetic industry and customer loyalty, particularly in local cosmetic product. This proposal hopes to contribute to cosmetic industry and customer and provides insights to marketing researchers in understanding the influence of business ethics and customer loyalty. Hence there is no findings reported in this paper since this is a conceptual paper.